Association of the type of 5q loss with complex karyotype, clonal evolution, TP53 mutation status, and prognosis in acute myeloid leukemia and myelodysplastic syndrome. Issue 5 (3rd February 2014) - Volkert, Sarah; Kohlmann, Alexander; Schnittger, Susanne; Kern, Wolfgang; Haferlach, Torsten; Haferlach, Claudia
<x xml:space="preserve">Abstract</x> We analyzed 1, 200 patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS) harboring a 5q deletion in order to clarify whether the type of 5q loss is associated with other biological markers and prognosis. We investigated all patients by chromosome banding analysis, FISH with a probe for EGR1 (5q31) and, if necessary, to resolve complex karyotypes with 24‐color‐FISH. Moreover, 420 patients were analyzed for mutations in the TP53 gene. The patient cohort was subdivided based on type of 5q loss: Patients with interstitial deletions and patients with 5q loss due to unbalanced rearrangements or monosomy 5. Loss of the long arm of chromosome 5 due to an unbalanced rearrangement occurred more often in AML (286/627; 45.6%) than MDS (188/573; 32.8%; P < 0.001). In both entities, patients with 5q loss due to unbalanced translocations showed complex karyotypes more frequently (MDS: 179/188; 95.2% vs. 124/385; 32.2%; P < 0.001; AML: 274/286; 95.8% vs. 256/341; 75.1%; P < 0.001). Moreover, in MDS unbalanced 5q translocations were associated with clonal evolution (109/188; 58.0% vs. 124/385; 32.2%; P < 0.001), mutation of TP53 (64/67; 95.5% vs. 40/120; 40.0%; P < 0.001), and shorter survival (15.3 months vs. not reached; P < 0.001). In MDS, complex karyotype was an independent adverse prognostic factor (HR = 5.34; P = 0.032), whereas in AML presence of TP53 mutations was the strongest adverse prognostic factor (HR = 2.21; P = 0.026). In conclusion, in AML and MDS, loss of the long arm of chromosome 5 due to unbalanced translocations is associated with complex karyotype and in MDS, moreover, with clonal evolution, mutations in the TP53 gene and adverse prognosis. © 2014 Wiley Periodicals, Inc.